2015
DOI: 10.1123/japa.2013-0104
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Age and Physical Activity Level on Manual Aiming Performance

Abstract: Older adults traditionally adapt their discrete aiming movements, thereby traveling a larger proportion of the movement under closed-loop control. As the beneficial impact of a physically active lifestyle in older age has been described for several aspects of motor control, we compared the aiming performance of young controls to active and sedentary older adults. To additionally determine the contribution of visual feedback, aiming movements were executed with and without saccades. Results showed only sedentar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 38 publications
1
10
0
2
Order By: Relevance
“…A strategy of undershooting downward movements to a greater extent than other movements appears to be even more pronounced in older adults (Bennett et al, 2012). This exaggerated 'play-it-safe' strategy in older adults is consistent with other findings in the literature which show that older adults often sacrifice movement speed to reduce final endpoint error and minimize energy expenditure (Ketcham et al, 2002; Goal-Directed Reaching 9 Poletti et al, 2015;Pratt et al, 1994;Van Halewyck et al, 2014, 2015a, 2015bWelsh et al, 2007).…”
Section: Goal-directed Reachingsupporting
confidence: 82%
“…A strategy of undershooting downward movements to a greater extent than other movements appears to be even more pronounced in older adults (Bennett et al, 2012). This exaggerated 'play-it-safe' strategy in older adults is consistent with other findings in the literature which show that older adults often sacrifice movement speed to reduce final endpoint error and minimize energy expenditure (Ketcham et al, 2002; Goal-Directed Reaching 9 Poletti et al, 2015;Pratt et al, 1994;Van Halewyck et al, 2014, 2015a, 2015bWelsh et al, 2007).…”
Section: Goal-directed Reachingsupporting
confidence: 82%
“…brain atrophy, altered brain connectivity) (Guttmann et al, 1998;Raz et al, 2005;Davis et al, 2012). Age-related movement deficits are already present during simple point-to-point reaching movements, occurring as increased spatial and temporal movement variability and movement slowing (Darling et al, 1989;Yan et al, 1998;Ketcham et al, 2002;Van Halewyck et al, 2015). Apart from the movement parameters that are altered with aging, controlling movement might also impose increased cognitive demand on older…”
Section: Introductionmentioning
confidence: 99%
“…As the size of the medium target was not vastly different to either the large or small target, the focus of the strategy could have been either speed or accuracy. Indeed, contemporary research (Van Halewyck et al 2014 ) has reported no age related differences in primary saccade amplitude when tasks that only differ by an ID of 1 bit are used. The medium target was therefore excluded from the analysis to remove any confound related to task strategy.…”
Section: Methodsmentioning
confidence: 99%